4.8k views
1 vote
8(11k-8)-8=8(-9+11k)

2 Answers

3 votes

Multiply the first bracket by 8.

Multiply the second bracket by 8.

8(11k-8)-8=8(-9+11k)

88k-64-8= -72+88k

88k-72= -72+88k

Move -72 to the right side. Sign changes from -72 to +72.

88k-72+72= -72+72+88k

88k= 88k

Answer : all real numbers

User Mobrockers
by
5.5k points
5 votes

Answer:

The equation has infinite solutions

Explanation:

We have the following expression


8(11k-8)-8=8(-9+11k)

To solve the equation apply the distributive property


8*11k-8*8-8=-9*8+11*8k

Now simplify the expression


88k-64-8=-72+88k


88k-72=-72+88k


0=0

The equation has infinite solutions

User Brian Webb
by
4.9k points